Inhibition of ice recrystallization by tamarind (Tamarindus indica L.) seed polysaccharide and molecular weight effects. (1st February 2023) - Sun, Xianbao; Guo, Rui; Kou, Yuxing; Song, Hong; Zhan, Taijie; Wu, Jinhong; Song, Lihua; Zhang, Hui; Xie, Fan; Wang, Jiangmei; Song, Zibo; Wu, Yan
Abstract: This study aimed to investigate the inhibition effects of tamarind seed polysaccharide (TSP) on ice recrystallization and to figure out its possible molecular weight-dependent effects. TSP fractions (2412.38–20.75 kDa) were prepared while preserving the natural structure. Ice recrystallization was effectively inhibited by TSP. Decreasing the molecular weight to a certain range, such as 224.04 kDa and 90.41 kDa, could enhance the activity of TSP due to the reduction of self- and intermolecular aggregation. Adding TSP into water decreased the melting temperature of bulk ice. Raman spectra showed that partial group vibrations or deformations of TSP molecules were restricted upon solution freezing and also revealed a destructuring effect of TSP on the H-bond network of water. These findings suggested the potential of TSP as a novel food cryoprotectant and help produce TSP fractions with enhanced activity, and shed new light on understanding the antifreeze mechanism of natural polysaccharides. Graphical abstract: Unlabelled Image